The Research Driven Cluster Initiative. Challenges and opportunities for cluster approaches in the Mediterranean - Noetzel R.; Kunze U.; Ditgens B. (Moving forward in the Euro-Mediterranean Research and Innovation partnership. The experience of the MIRA project, 2013)
There is a huge potential for transnational cluster initiatives in the Mediterranean Countries. In the frame of the networking project MIRA, the activities for the promotion and the development of a “Research Driven Cluster Initiative (RDCI) on Water and Waste Water Management in the Mediterranean” are considered as an appropriate approach to tackle the cross-border problems of integrated water management and water pollution in the Mediterranean macro-region. Taking into account the conditions and possibilities of the MIRA project, the efforts of the cluster development approach were focussed rather on the promotion of a cluster initiative and not so much on the establishment of clusters. This was done by introducing the relevance of a clustering approach, by analysing initial competencies and clusters, and by building a leadership group. This initiative is being carried out in the frame of the EMIS (Euro-Mediterranean Innovation Space) activities. Different events such as Innovation Forums and a Cluster Mission were organised which are described in the following text.